Contemporary minimal invasive surgical management of stones in children - Rasim Güzel; Ümit Yildirim; Kemal Sarica (Asian Journal of Urology)
Objective: Pediatric urolithiasis has been more common over the past 20 years, and urologists have unique challenges in managing it surgically because this particular demographic is recognized as one of the high-risk categories for stone recurrence. Given this reality, care focuses on maintaining renal function, achieving total stone-free status, and most importantly avoiding stone recurrences. In this presented article, we aimed to make a comprehensive review of the current minimally invasive treatment of pediatric kidney stone disease. Methods: We evaluated the results of 74 studies following a comprehensive PubMed search till February 2023. This article was written by making use of current urology guidelines. Results: Considering the reported occurrence of metabolic issues in up to 50% of cases in addition to the anatomic anomalies (about 30% of cases), the treatment of pediatric urolithiasis necessitates a full metabolic and urological examination on an individual basis. Timely management of metabolic imbalances and obstructive diseases is necessary. In addition to encouraging proper fluid consumption, it is advisable to improve urine volume and consider using medical therapeutics to raise urinary citrate levels. The location, content, and size of the stone(s), the morphology of the collecting system, the presence of urinary tract infection, as well as the presence of any obstruction, should all be taken into consideration while deciding on the best surgical procedure. Conclusion: All modern endourological methods are now used in the safe and efficient care of pediatric urolithiasis as a consequence of the obvious advancements in instrument technology and expanding expertise derived from adult patients. Other minimally invasive procedures, such as ureterorenoscopy and percutaneous nephrolithotomy, require more expertise and can be successfully applied with careful management for an excellent stone-free rate with minimal morbidity. Of these procedures, shock wave lithotripsy is still the first choice in the majority of cases with upper tract calculi. Open surgery will still be the therapy of choice for pediatric patients with complicated and big stones as well as anatomical anomalies.